Lobectomy versus sublobar resection on survival in patients with stage T1-2N0M0 small cell lung cancer - Xue Yin; Huan-Wei Liang; Yang Liu; Wei Huang; Xin-Bin Pan (PLoS ONE, 2025)
Purpose To compare survival outcomes of lobectomy versus sublobar resection in patients diagnosed with stage T1-2N0M0 small cell lung cancer (SCLC). Materials and methods A comprehensive retrospective analysis was conducted using data from the Surveillance, Epidemiology, and End Results database. The Kaplan-Meier method was utilized to estimate cancer-specific survival (CSS) and overall survival (OS) between stage T1-2N0M0 SCLC patients undergoing sublobar resection and those receiving lobectomy. Results A total of 185 patients were included in the analysis, with 64 undergoing sublobar resection and 121 receiving lobectomy. Before propensity score matching, lobectomy was associated with significantly better CSS (hazard ratio [HR] =, 95% confidence interval [CI]: 0.32, P = 0.006) and OS (HR =, 95% CI: 0.39, P = 0.005) compared to sublobar resection. Multivariable Cox regression analysis confirmed that lobectomy was an independent predictor of improved CSS (HR =, 95% CI: 0.24, P = 0.003) and OS (HR =, 95% CI: 0.36, P = 0.013). After propensity score matching, the differences in CSS (HR =, 95% CI: 0.36, P = 0.177) and OS (HR =, 95% CI: 0.46, P = 0.234) between the two surgical approaches were not statistically significant, Conclusion Lobectomy may offer improved survival outcomes compared to sublobar resection in patients with stage T1-2N0M0 SCLC.